Evidence for a Role for Phospholipase C, but not Phospholipase A2, in Platelet Activation in Response to Low Concentrations of Collagen - Lockhart, Leslie K.; Pampolina, Caroline; Nickolaychuk, Brent R.; McNicol, Archibald (Thrombosis and Haemostasis, 2001)
The release of arachidonic acid is a key component in platelet activation in response to low concentrations (1-20 g/ml) of collagen. The precise mechanism remains elusive although a variety of pathways have been implicated. In the present study the effects of inhibitors of several potentially key enzymes in these pathways have been examined. Collagen (1-10 g/ml) caused maximal platelet aggregation which was accompanied by the release of arachidonic acid, the synthesis of thromboxane A2, and p38MAPK phosphorylation. Preincubation with the dual cyclooxygenase/lipoxygenase inhibitor BW755C inhibited aggregation and thromboxane production, and reduced p38MAPK phosphorylation. A phospholipase C inhibitor, U73122, blocked collagen-induced aggregation and reduced arachidonic acid release, thromboxane synthesis and p38MAPK phosphorylation. Pretreatment with a cytosolic phospholipase A2 inhibitor, AACOCF3, blocked collagen-induced aggregation, reduced the levels of thromboxane formation and p38MAPK phosphorylation but had no significant effect on arachidonic acid release. In contrast inhibition of PKC by Rö31-8220 inhibited collagen-induced aggregation, did not affect p38MAPK phosphorylation but significantly potentiated arachidonic acid release and thromboxane formation. Collagen caused the tyrosine phosphorylation of phospholipase C 2 which was inhibited by pretreatment with U73122, unaffected by AACOCF3 and enhanced by Rö31-8220. These results suggest that cytosolic phospholipase A2 plays no role in the arachidonic acid release in response to collagen. In contrast, the data are consistent with phospholipase C 2 playing a role in an intricately controlled pathway, or multiple pathways, mediating the release of arachidonic acid in collagen-stimulated platelets.
Keywords: Platelets; collagen; arachidonic acid; phospholipase